Avoiding antibiotics in the management of recurrent UTIs in women: What are our options?. (January 2020) - Yang, Bob; Blick, Christopher; Foley, Steve
Urinary tract infections are one of the most common infections worldwide, accounting in the United Kingdom for 1–3% of all medical consultations. Fifty per cent of women will experience one episode of urinary tract infection in their lifetimes and of these, up to 30% will develop recurrent urinary tract infections. Such women often rely on long-term low dose antibiotics. Level of evidence: Not applicable for this multicentre audit.